2019
DOI: 10.1177/0969733019874495
|View full text |Cite
|
Sign up to set email alerts
|

The compassion levels of midwives working in the delivery room

Abstract: Background: Compassion-based practices in midwifery are the most important expression of the depth of care quality. This concept is insufficiently represented in literature, therefore, studies on this subject are of utmost importance. Objectives: This study aims to determine the levels of compassion of midwives working in the delivery room and the factors affecting these levels. The study was carried out in Kocaeli, Turkey. Methods: This descriptive study was carried out from 1 February to 15 April 2019 in del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 25 publications
(41 reference statements)
0
17
0
Order By: Relevance
“…Dissatisfaction with remuneration leads to job dissatisfaction, which negatively affects the compassion levels of midwives, as supported by a study by Ergin et al [34] on the compassion levels of midwives working in the delivery room.…”
Section: Reduced Confidencementioning
confidence: 83%
“…Dissatisfaction with remuneration leads to job dissatisfaction, which negatively affects the compassion levels of midwives, as supported by a study by Ergin et al [34] on the compassion levels of midwives working in the delivery room.…”
Section: Reduced Confidencementioning
confidence: 83%
“…The increase in the indifference subdimension scores indicates that individuals are more insensitive to events (Pommier, 2011). In another study, those who worked 11 or more extra hours per month obtained significantly higher scores on the indifference subdimension (Ergin et al, 2019). In this study, indifference scores increased in parallel with the number of traumatic births the midwives had been exposed to.…”
Section: Discussionmentioning
confidence: 95%
“…Past studies have examined midwives' perceptions of compassion and spiritual care. However, these studies are limited to only a few populations, contexts, societies and cultures (Ergin et al, 2019; Gönenç et al, 2016; Moloney & Gair, 2015). Studies conducted in different cultures are needed to determine the factors that affect the level of spiritual care and compassion of midwives around the world.…”
Section: Introductionmentioning
confidence: 99%
“…The compassion scale score has been found as 94.63±11.58 among all midwifery students. Ergin et al have found the compassion scale score of midwives working in the delivery high (23). Total compassion point is influenced by the professional factors such as total compassion point, number of patients, rotating shift work, number of traumatic births and job satisfaction (23).…”
Section: Discussionmentioning
confidence: 99%
“…Ergin et al have found the compassion scale score of midwives working in the delivery high (23). Total compassion point is influenced by the professional factors such as total compassion point, number of patients, rotating shift work, number of traumatic births and job satisfaction (23). In this study, it has been found that the total point of compassion scale has been affected only by the marital status; and the compassion levels of the single students have been significantly higher than those of the married students.…”
Section: Discussionmentioning
confidence: 99%